Renewable Energy Policy Framework for Sustainable Power Supply: An Empirical Assessment of Obafemi Awolowo University, Nigeria - Etebom John Monday; Adeyemo Isaiah Adedayo; Olawale Olalekan Oluyinka; Adebayo Paul Olumoroti (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2026)
University campuses in developing nations face critical energy sustainability challenges, with implications for academic performance, operational efficiency, and environmental stewardship. This study examines the development of a comprehensive renewable energy policy framework for Obafemi Awolowo University (OAU), Nigeria, which currently consumes 6.0 MW of electricity with frequent disruptions from the national grid. Using a mixed-methods approach, we analyzed energy consumption patterns across 180 facilities, assessed renewable energy potential through solar irradiation data (average 16.68 MJ/m² per day for Ile-Ife region), and evaluated stakeholder perceptions through surveys (n=425) and interviews (n=35). Quantitative analysis revealed peak energy demand of 7.2 MW during academic sessions, with significant inefficiencies in aging infrastructure (68% of electrical systems over 30 years old). Cost-benefit analysis demonstrates that a hybrid solar-grid system could reduce energy costs by 42% (approximately ₦420 million annually) while achieving carbon emission reductions of 4,200 tonnes CO₂ equivalent per year. The proposed policy framework integrates technical specifications, financial mechanisms, and governance structures to achieve 60% renewable energy penetration by 2030. Statistical analysis using regression modeling (R²=0.87) identified key predictors of energy consumption, while geospatial assessment confirmed optimal solar panel placement sites covering 12,000 m². This research contributes to sustainable energy transition strategies for higher education institutions in sub-Saharan Africa, providing a replicable model for energy policy development and implementation.